Prevalence of second hand smoke exposure among adults in Bulawayo, Zimbabwe - Ndlovu, Nkanyiso (My University, 2016)
Introduction: Annually, hundred thousands of people worldwide die as a result of second hand smoke (SHS) exposure. There is no safe exposure level to SHS yet in Bulawayo, smokers have been observed smoking without restraint thus exposing non-smokers to SHS. The purpose of this study was to establish the prevalence and contributing factors of SHS exposure among adults in Bulawayo, Zimbabwe. Methods: A cross sectional study was conducted and participants were randomly selected from residents who visited the 13 municipal revenue halls. A structured questionnaire was used to collect data from respondents. Descriptive and multivariate logistic regression analyses were performed. Results: Home SHS exposure prevalence was 22% and females were 2.11 times more likely than males to be exposed at home. Prevalence of SHS exposure in public transportation, health facilities, educational and food premises was 40.9%, 26.3%, 42,9% and 36.8% respectively. Conclusion: SHS exposure in Bulawayo was high and there is need to reduce SHS exposure to non-smoking adults. Keywords: Second hand smoke (SHS), Bulawayo, Prevalence, Exposure, Adult
Thesis (MPH.) -- University of Limpopo, 2016.
Keywords: Second hand smoke; Smoking; Smoking; Tobacco smoke pollution; Tobacco smoke pollution -- Health aspects -- Zimbabwe; Passive smoking